Developing Affective Model for Measuring and Managing Customer Satisfaction in Container Ports - Neysi, Abdolhossein; Dadkhah, Abolfazle (Journal of Asian Business Strategy, 2013)
Nowadays changes in global trade and Maritime transportation always will create competition between ports. Following this competition will be absorption of goods, and it will bring about economic boom. It is therefore appropriate to provide facilities to increase satisfaction of Shipping Lines, which in turn can attract the many shipping lines to port and the port will increase their allegiance. Aimed to identification of factors affecting the extent of satisfaction of container shipping lines from port services as well as prioritization of the factors affecting customer satisfaction in Iraqi container ports, this research has been implemented. Based on the objective, the present research is an applied one as it uses the principles and tactics - formulated in basic researches - for solution of actual and executive problems of Iraqi container ports. Kano model is applied to reach to the objectives of research. Finally, the indicators affecting shipping lines customers? satisfaction were determined and classified according to Kano model. Coefficients of satisfaction and dissatisfaction were estimated and prioritized for each one.